No effect of subperiosteal growth factor application on periosteal neo-chondrogenesis in osteoperiosteal bone grafts for osteochondral defect repair - Gotterbarm, Tobias; Breusch, Steffen J.; Vilei, Simona Berardi; Mainil-Varlet, Pierre; Richter, Wiltrud; Jung, Martin (International orthopaedics, 2013)
The purpose of this study was to examine the effect of subperiosteal injection of chondroinductive growth factors on the histological and biomechanical outcome of autologous osteoperiosteal grafts.
Gesehen am 19.02.2020